The Relationship Between Family-Work Conflict and Work-Family Conflict Among Special Education Teachers - Zainab Canu (Jurnal Multidisiplin Madani, 2023)
Special education teachers are a big part of how students with disabilities learn. Because of conflicts between work and family and family and work, special education teachers are less happy with their jobs than other teachers. This study looks at the work-family, work-family, and job satisfaction of special education teachers in Kottayam. Sixty special education students from Sulawesi were used in this study. This research is about describing things. The standard questionnaire collects data. Teachers were unhappy with their jobs, and there was a strong link between WFC and FWC (p=.000). (p=.000) FWC influences job satisfaction. The project's main goal is to make it easier for special educators to do their jobs. Their low incomes and lack of education keep them from getting help from the government, which hurts their mental health and potential. Teachers, especially those who teach kids with special needs, help kids grow. People who work in schools help kids who have trouble learning. Special school teachers have to deal with more stress and pressure than other teachers. So, it is crucial to find out if these things are causing problems in their personal, professional, and family lives. So, teachers must teach and help students with disabilities in regular classes. Special education teachers must work harder than other teachers to help students with special needs. Special education teachers help disabled kids succeed by being their second parents, advisors, and counsellors. These teachers must figure out how to balance their personal lives with their jobs. Most people have trouble keeping their personal and work lives in balance. They find it hard to meet both their personal and professional obligations. Human relations are the ways that people get along with each other. The human relations model was made by Elton Mayo, Mary Parker Follet, and Robert Owen. It is based on the idea that workers are motivated not only by money, but also by praise, recognition, a sense of belonging, victory or achievement, and pride and honor in their work. Focusing on people and relationships boosts morale and gets more work done. When employees feel welcome in the office, they work harder and are happier with their jobs. The same as these teachers. Policymakers and governments often do not care about them. This affects the quality and satisfaction of the job. Education, Teachers, Job Satisfaction, Interactions Between Work and Family, Work Conflicts, and Work